Interventions for children with neurocognitive impairments in resource-limited settings: A systematic review. (November 2020) - Van Pelt, Amelia E.; Lipow, Matthew I.; Scott, J. Cobb; Lowenthal, Elizabeth D.
Highlights: 19 articles evaluated cognitive support among youth in resource-limited settings. Interventions include caregiver training, cognitive training, exercise, and nutrition. The reported efficacy of interventions is not consistent. Evidence suggests that some interventions may improve cognitive function. Abstract: Many children and adolescents around the world suffer from neurocognitive deficits due to chronic disorders, such as Human Immunodeficiency Virus (HIV) and malaria. Resource-limited settings exacerbate the risk of negative cognitive outcomes due to high prevalence of associated disorders, poverty, and limited access to interventions. Current literature does not provide consensus regarding the efficacy of interventions to support children with cognitive impairments in low-resource settings. This research aimed to identify and evaluate interventions for youth with neurocognitive deficits in resource-limited settings. A systematic review of peer-reviewed literature was conducted within five databases (PubMed, Web of Science, CINAHL, PsycInfo, and WHO Index Medicus). Cognitive impairment was broadly defined to be inclusive of aspects of intellectual and cognitive functioning (e.g., working memory, attention, executive function). The income status of the country or countries in which each study was located was determined according to World Bank Income Status. Studies conducted in countries classified as low- or middle-income were included. Since low-resource areas exist within high-income countries, the resource availability within study settings in high-income countries was systematically evaluated for inclusion. The search yielded 19 articles that met all inclusion criteria. Interventions included strategies involving caregiver training, computerized and non-computerized cognitive training, physical activity, and nutritional supplementation. Interventions were administered in medical facilities, educational facilities, or the home. The majority of the interventions targeted the domains of memory and attention. Overall, the efficacy of interventions was inconsistent. Further, results indicated that the relationship between cognitive improvement and intervention types was not consistent across cognitive domains. However, when evaluating studies on an individual basis, some strategies demonstrated clinically- and statistically-significant improvement in cognitive function among specific groups of children. The low article yield highlights that few researchers have evaluated pediatric cognitive support interventions in low-resource contexts. This review suggests support strategies that should be considered for future studies as neurocognitive screening capacity improves in resource-limited settings.